The Success of School Leadership Style in Improving Non-Academic Achievement of Students - Arzadi, Muh Pathoni; Budiartati, Emmy; Hudallah, Noor (Educational Management, 2021)
The leadership style of the principal can be described in various labels, for example the principal is generous, stubborn and straightforward, convincing and others. Today, educational institutions need a leadership style that is transformative and capable of seeing opportunities for change and development in modern times. This study aims to analyze the principal's leadership style in increasing the non-academic achievement of students at MA DarulMahmudien. This type of research is descriptive qualitative with a case study approach. The samples in this research were the principal and teachers who were taken by purposive sampling technique. Data collection techniques using interviews, observation and document study. Data analysis used the stages of data reduction, data presentation and drawing conclusions. The results showed that the principal's leadership style was transformative and democratic. This can be seen from his ability to manage school management from planning to evaluation. In addition, it can be seen from his daily behavior in establishing relationships with fellow teachers and with other employees. The leadership of the MA DarulMahmudien principal is able to increase teacher motivation and student non-academic achievement, which is evidenced by the various achievements obtained by students in several sports fields at the sub-district, provincial or national level. The conclusion is that the leadership of the principal of MA DarulMahmudien has been effective in increasing students' non-academic achievement by taking various steps.